Isoprenaline enhances local Ca2+ release in cardiac myocytes - Shen Jian-xin (Acta Pharmacologica Sinica, 2016)
Aim: Contraction of cardiac myocytes is controlled by the generation and amplification of intracellular Ca2+ signals. The key step of this process is the coupling between sarcolemma L-type Ca2+ channels (LCCs) and ryanodine receptors (RyRs) in the sarcoplasmic reticulum (SR). β-Adrenergic stimulation is an important regulatory mechanism for this coupling process. But the details underlied the global level, which require local Ca2+ release study are still unclear. The present study is to explore the effects of β-adrenergic stimulation on local Ca2+ release. Methods: Using confocal microscopy combined with loose-seal patch-clamp approaches, effects of isoprenaline (1 μmol·L-1), a β-adrenergic agonist, on local SR Ca2+ release triggered by Ca2+ influx through LCCs in intact rat cardiac myocytes were investigated. Results: Isoprenaline increased the intensity of ensemble averaged local Ca2+ transients, the peak of which displayed a typical bell-shaped voltagedependence over the membrane voltages ranging from ~-40mV to ~+35mV. Further analysis showed that this enhancement could be explained by the increased coupling fidelity (which refers the increased probability of RyRs activation upon depolarization), and the increased amplitude of evoked Ca2+ sparks (due to more Ca2+ releases through local RyRs). In addition, isoprenaline decreased the first latency, which displayed a typical “U”-shaped voltage-dependence, showing the available acceleration and synchronization of β-adrenergic stimulation on intracellular calcium release. Conclusions: Isoprenaline enhances local Ca2+ release in cardiac myocytes. These results underscore the importance of regulation of β-adrenergic stimulation on local intermolecular signals between LCCs and RyRs in heart cells.